Implementing ChatGPT in Teaching Insya' to Intermediate-Level Students: Enhancing Arabic Composition Skills - Ali Mukmin, Torang; Khoirun, Fattah; Hakim, Wildan; Maksum, M. Syukron; Aminudin (Al-Qalam Institue, 2025)
The integration of Artificial Intelligence (AI), specifically ChatGPT, into the teaching of Arabic composition (insya) in pesantren (Islamic boarding schools) offers significant potential for enhancing the quality and efficiency of Arabic language education. This study aims to explore the effectiveness of ChatGPT in improving the Arabic writing skills of santri at the mutawassith (middle) level in pesantren. The research employs a qualitative, descriptive phenomenological approach, using semi-structured interviews, participatory observations, and focus group discussions to gather data. The findings reveal that while ChatGPT enhances student engagement and provides real-time feedback that improves grammatical accuracy, challenges such as limited access to technology, lack of technical competence, and concerns over cultural nuances and plagiarism remain. The study highlights the need for a collaborative approach involving educators, students, and AI developers to address these barriers. It contributes to the understanding of AI’s role in Islamic education, particularly in Arabic composition, and emphasizes the importance of blending AI tools with traditional pedagogical methods for a holistic learning experience. Future research should explore the long-term impacts of AI on language proficiency and cultural understanding.